Hepatic and portal vein Doppler ultrasounds in assessing liver inflammation and fibrosis in chronic HBV infection with a normal ALT level - Tian, Li; Tang, Shuyao; Wang, Na; Deng, Huan; Zhang, Qunxia; Shi, Tongdong (Frontiers in Medicine, 2023)
Aims To discuss the clinical value of hepatic and portal vein Doppler ultrasounds in assessing liver inflammation and fibrosis in patients with chronic hepatitis B virus (HBV) infection, and a normal alanine transaminase (ALT) level. Methods 94 patients with chronic HBV infections who had undergone ultrasound-guided liver biopsies were enrolled and grouped by the liver tissue pathological results. Analyzed the differences and correlation between parameters of the hepatic and portal vein Doppler ultrasounds are discussed across different degrees of liver inflammation and fibrosis. Results There were 27 patients with no significant liver damage and 67 patients with significant liver damage, there were significant differences in the parameters of the hepatic and portal vein Doppler ultrasounds between them (p < 0.05). As liver inflammation was aggravated, the inner diameter of the portal vein increased, and the blood flow velocities of the portal and superior mesenteric veins decreased (p < 0.05). When liver fibrosis became more severe, the inner diameter of the portal vein increased, while the blood flow velocities of the portal, superior mesenteric, and splenic veins decreased, and the Doppler waveforms of hepatic veins became unidirectional or flat (p < 0.05). The receiver operating characteristic (ROC) curve showed the assessment efficacy of hepatic and portal vein Doppler ultrasounds was superior to abdominal Doppler ultrasound alone in assessing liver fibrosis, and the combination of the two examination techniques outperformed any technique used alone. Conclusion The hepatic and portal vein Doppler ultrasounds have important clinical value for assessing liver fibrosis in patients with chronic HBV infection, to aid improve the diagnosis of liver fibrosis.